DAMPAK PERNIKAHAN DINI TERHADAP KESEHATAN REPRODUKSI - Wulandari, Sinta; Erdiansyah, Figar Nebi; Sari, Elvi Kumala; Wardhani, Hanifian Listi Eka; Pangestika, Putri Dyah Ayu; Febrianty, Shabilla Nur; Prasetyo, Tegar Dwi (Jurnal Keperawatan Duta Medika, 2024)
Marriage is a physical and spiritual bond between a man and a woman to have children, which is carried out according to Islamic law with the aim of forming a harmonious and eternal family based on God Almighty. Basically marriage is carried out by someone who has maturity in terms of physical, psychological and economic. However, most Indonesian citizens still find marriages that have not been accompanied by readiness from various aspects such as physical, psychological and economic. This article uses descriptive research methods and qualitative research which will dig deeper into early marriage and its relation to reproductive health. Early marriage is carried out by someone who is under the age of 19 who is not ready from various aspects. This is likely to have an impact on the reproductive health of both women and men. Therefore, it is necessary to be prepared from various aspects in carrying out marriages so as to avoid the adverse effects of early marriage on reproductive health. Â